Islamic Clothing, Religiosity, and Da'wah Communication - Abidin, Kurniati; Zainuddin, Rasyidah; Burchanuddin, Andi; Kamaruddin, Syamsu (State Islamic Institute of Bone, Indonesia, 2021)
Clothing is one of the results of human culture which has many functions such as health functions, ethical functions, and aesthetic functions. At the same time, clothing also gives the impression to the public as a form of communication inherent in it. This article aims to reveal clothes with the impression of communication to others. One of the clothes referred to is Muslim clothing which includes a robe, robe, turban, cingkrang pants (for men), and a headscarf (for women). This research method uses descriptive quantitative method with 50 respondents consisting of 25 men and women each. The results showed that Muslim clothes gave many impressions such as the impression of faith, the impression of sunnah, the impression of syar'i and so on. The conclusion of this research is that clothes always leave an impression and message. These impressions and messages are received by the public as a form of communication for the wearer. Muslim clothing gives the impression of religiosity and spirituality.